Morality in intergroup conflict - Halevy, Nir; Kreps, Tamar A.; Weisel, Ori; Goldenberg, Amit (Elsevier, 2015)
Intergroup conflict encompasses a broad range of situations with moral relevance. Researchers at the intersection of social and moral psychology employ diverse methodologies, including surveys, moral dilemmas, economic games, and neuroimaging, to study how individuals think, feel, and act in intergroup moral encounters. We review recent research pertaining to four types of intergroup moral encounters: (a) value-expressive and identity-expressive endorsements of conflict-related actions and policies; (b) helping and harming ingroup and out-group members; (c) reacting to transgressions committed by in-group or out-group members; and (d) reacting to the suffering of in-group or out-group members. Overall, we explain how sacred values, social motives, group-based moral emotions, and the physiological processes underlying them, shape moral behavior in intergroup conflict.